If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = 2x + 9 Reorder the terms: -4 + 7x = 2x + 9 Reorder the terms: -4 + 7x = 9 + 2x Solving -4 + 7x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 7x + -2x = 9 + 2x + -2x Combine like terms: 7x + -2x = 5x -4 + 5x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 5x = 9 + 0 -4 + 5x = 9 Add '4' to each side of the equation. -4 + 4 + 5x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 9 + 4 5x = 9 + 4 Combine like terms: 9 + 4 = 13 5x = 13 Divide each side by '5'. x = 2.6 Simplifying x = 2.6
| 450000+-22000x=-155000+12 | | 4x+(-4)+1+(-3x)=3x+(-3)+4 | | 74+p=-68 | | 7c-6=-104 | | -11x-8=-10x+19 | | 23t-31=3t-15 | | -3+(-6p)=3(5+4p) | | 4(x+1)-2(2x-3)=10 | | 8(t-2)+4t=6(2t+2)-10 | | 5=f-19 | | 32x-6=14 | | 3x+12-9x=11-6x | | (7x-8)= | | 4x+y=-23 | | 3/4b-7=8 | | -8+(1r)=8(r-1) | | Y^2+10y+35=0 | | 9x+10-7x-4= | | 7*11= | | y=(9x+7)(x-3) | | 2(3a-9)=2a-1x(a-1) | | 4x^3+16x^2-8x= | | 14-19x+3x^2=0 | | -x/5+2=x/5+7 | | 7-5/2x=9 | | -24*2= | | X+2x+c=43 | | -81+6x=x+39 | | 5(y+1)=-8 | | 3c-2=8 | | -7x+8+4x=-3(x-3)-1 | | N=24 |